Fault Attack on ACORN v3. (8th May 2018) - Zhang, Xiaojuan; Feng, Xiutao; Lin, Dongdai
Abstract: Fault attack is one of the most efficient side channel attacks and has attracted much attention in recent public cryptographic literatures. In this work, we introduce a fault attack on the authenticated cipher ACORN v3. Our attack is done under the assumption that a fault is injected into an initial state of ACORN v3 randomly, and contains two main steps: fault locating and equation solving. At the first step, we introduce concepts of unique set and non-unique set, where differential strings belonging to unique sets can determine the fault location uniquely. For strings belonging to non-unique sets, we use some strategies to increase the probability of determining the fault location uniquely to almost 1. At the second step, we demonstrate several ways of retrieving equations, and then obtain the initial state by solving equations with the guess-and-determine method. With n fault experiments, we can recover the initial state with time complexity c ⋅ 2 146.5 − 3.52 ⋅ n, where c is the time complexity of solving linear equations and 26 < n < 43 . We also apply the attack to ACORN v2, which shows that the changes from ACORN v2 to ACORN v3 have reduced the security margin of this algorithm against the differential fault attack.